2012
DOI: 10.1002/ijc.27508
|View full text |Cite
|
Sign up to set email alerts
|

Influences of tobacco and alcohol use on hepatocellular carcinoma survival

Abstract: Prognosis of hepatocellular carcinoma (HCC) is generally poor. The role of modifiable lifestyle factors on HCC survival has been less studied. To examine whether prediagnosis smoking and alcohol affected HCC survival stratified by viral etiology, we conducted a prospective cohort study of 2,273 (1990 with viral hepatitis and 283 without) incident HCC cases aged 20-75 years who were enrolled between 1997 and 2004 from a Taiwanese multicenter study, and followed up through 2007. Information on habitual smoking a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 36 publications
(78 reference statements)
1
49
2
Order By: Relevance
“…These data are in contrast with two recent Asian studies that found an association between tobacco use and recurrence after surgery and overall survival in HBV/HCV-related HCC [15,16]. However, because continued smoking after HCC treatment may be more relevant than smoking before HCC diagnosis, data on post-treatment smoking habit are needed.…”
Section: Page 12 Of 27contrasting
confidence: 66%
See 1 more Smart Citation
“…These data are in contrast with two recent Asian studies that found an association between tobacco use and recurrence after surgery and overall survival in HBV/HCV-related HCC [15,16]. However, because continued smoking after HCC treatment may be more relevant than smoking before HCC diagnosis, data on post-treatment smoking habit are needed.…”
Section: Page 12 Of 27contrasting
confidence: 66%
“…A c c e p t e d M a n u s c r i p t 4 Tobacco smoking has been recognized as a risk factor for various cancers, including HCC [14]; further, two recent investigations [15,16] found an association between continued smoking after diagnosis and worse prognosis for HCC Lastly, hypertension has been investigated as a possible independent predictor of HCC survival [17], although more conclusive data are required.…”
Section: Page 4 Of 27mentioning
confidence: 99%
“…Another reason for the difference in incidence in different regions was Human papillomavirus (HPV), which is responsible for stomach, liver and cervical cancers (Vineis and Wild, 2014). Other etiologies for liver cancer are modifiable risk factors, such as smoking, alcohol, contaminated injections in health care centers, immigration and obesity (Chuang et al, 2009;Ezzati and Riboli, 2013;Franceschi and Wild, 2013;Shih et al, 2012). The relative risk associated with family history of liver cancer is 2.6 and the cancer is also significantly more common in men (Huang et al, 2011;Yang et al, 2014).…”
Section: Incidence and Mortality Of Liver Cancer In The Wordmentioning
confidence: 99%
“…In both genders combined, dose-response analyses show RRs of 1.07 (95%CI: 1.04-1.10), 1.38 (95%CI: 1.28-1.50) and 1.82 (95%CI: 1.41-2.35) at 10, 50 and 100 g/day of alcohol consumption, respectively [43]. Associations of alcohol consumption with hepatocellular carcinoma are generally found at high intakes [44] with significant increased risks of about 30-40% at consumption levels >40 g/day [45][46][47][48]. An increased risk at low to moderate alcohol consumption is also reported [4,47,49].…”
Section: Neoplasms Of the Lower Digestive Tract: Colorectum And Livermentioning
confidence: 93%